Clinical and functional characteristics of OSA in children with comorbid asthma treated by leukotriene receptor antagonist: A descriptive study - Duong-Quy, Sy; Nguyen-Hoang, Yen; Nguyen-Ngoc-Quynh, Le; Nguyen-Thi-Phuong, Mai; Nguyen-Thi-Bich, Hanh; Le-Thi-Minh, Huong; Nguyen-Thi-Dieu, Thuy (Frontiers in Neurology, 2023)
Background Obstructive sleep apnea (OSA) is the most common form of respiratory disorders during sleep in children, especially those with severe asthma. However, optimal treatment of asthma might significantly improve OSA severity. Methods It was a cohort study including children aged >5 years old and diagnosed with asthma according to GINA (Global Initiative for Asthma). The data related to age, gender, height, weight, body mass index (BMI), clinical symptoms and medical history of asthma, spirometry (FEV1: forced expiratory in 1 s), and exhaled nitric oxide (FENO) were recorded for analysis. Respiratory polygraphy (RPG) was done for each study subject to diagnose OSA and its severity. Results Among 139 asthmatic children, 99 patients with OSA (71.2%) were included in the present study (9.3 ± 0.2 years): 58.6% with uncontrolled asthma and 32.3% with partial controlled asthma. The mean ACT (asthma control testing) score was 19.0 ± 3.4. The most frequent night-time symptoms were restless sleep (76.8%), snoring (61.6%), sweating (52.5%), and trouble breathing during sleep (48.5%). The common daytime symptoms were irritable status (46.5%) and abnormal behavior (30.3%). The mean AHI (apnea-hypopnea index) was 3.5 ± 4.0 events/h. There was a significant correlation between BMI and snoring index (R = 0.189 and P = 0.027), bronchial and nasal FENO with AHI (R = 0.046 and P < 0.001; R = 0.037 and P < 0.001; respectively). There was no significant correlation between asthma level, FEV1 and AHI. The severity of asthma and respiratory function were improved significantly after 3 months and 6 months of asthma treatment in combination with leukotriene receptor antagonist (LRA) treatment. The symptoms related to OSA were significantly improved after treatment with LRA. The severity of OSA was decreased significantly after 3 months and 6 months of treatment. Conclusion The treatment of asthmatic children with comorbid OSA by LRA in combination with standard therapy for asthma could improve the control of asthma and the symptoms and severity of OSA.